ANALISIS HUKUM ISLAM TERHADAP PEMENUHAN HAK DAN KEWAJIBAN DALAM RUMAH TANGGA (STUDI KASUS PADA ISTRI BERSTATUS PEGAWAI DI RS KABUPATEN BARRU) - zaldyputra; Muchsin, Agus; Haq, Islamul; Basri, Rusdaya; Rahmawati (IAIN BONE, 2025)
This study analyzes the fulfillment of marital rights and obligations of wives employed at Barru Regency Hospital from the perspective of Islamic Law and Indonesian Marriage Law. The research focuses on the implementation of spousal rights and obligations, influencing factors, and legal perspectives under Islamic and positive law. This qualitative study employs a case study approach, using primary data from employed wives at Barru Hospital and secondary data from relevant literature. Data were collected through observation, interviews, and documentation. The findings indicate a generally good level of cooperation between spouses in fulfilling their rights and obligations, despite challenges related to working hours and cultural norms. Cultural, educational, and economic factors significantly influence this fulfillment. The study emphasizes that marital rights and obligations should be carried out based on principles of justice, mutual respect, and cooperation in accordance with Islamic Law and statutory regulations.